Transformational Leadership in Public Education: Evaluating its Impact On Teacher Performance in Disadvantaged Areas - Ida Neka Impriasih; Tri Lestari Hadiati; Aris Toening Winarni (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study investigates the influence of transformational leadership on teacher performance in disadvantaged regions, with a specific focus on SMP Satu Atap Werdi in Pekalongan Regency. Schools located in remote and underdeveloped areas often face structural challenges such as limited resources, inadequate infrastructure, and geographical isolation, which significantly hinder the delivery of quality education. In this context, the role of school principals becomes critical in shaping organizational culture and motivating educators to maintain high performance despite the constraints. The research employed a qualitative descriptive approach, using participant observation, in-depth interviews, and document analysis to gather rich and comprehensive data from the principal and teachers as key informants. Findings indicate that even though SMP Satu Atap Werdi operates in an area with severely limited facilities, the transformational leadership style adopted by the principal has successfully brought about meaningful improvements in school management and teacher performance. The leadership was manifested through four main dimensions: idealized influence, demonstrated by strong role modelling and exemplary behaviour; inspirational motivation, reflected in the principal’s ability to encourage teachers to remain committed and enthusiastic; intellectual stimulation, which fostered creativity, innovation, and problem-solving among teachers; and individualized consideration, shown through personal guidance and support tailored to each teacher’s needs. These practices led to visible progress in teacher discipline, professional dedication, and organizational commitment. The study underscores the importance of transformational leadership as a catalyst for positive organizational change in education, particularly under challenging circumstances. The findings align with previous literature highlighting its effectiveness in motivating subordinates and enhancing performance. From a practical standpoint, this research suggests the need for policymakers and education stakeholders to strengthen transformational leadership practices in schools across disadvantaged regions as a strategy to achieve equitable educational quality in Indonesia.